Extract effect of Tintir (Jathropa Multifida Linn) to Total PMN and Selt Mast in Wound Healing Model Rats with Acute Injury - wahyuningsih, wahyuningsih (Universitas Wiralodra, 2019)
Wound is considered as a serious health problem, because it can interfere with quality of life due to pain, weakness, and decreased mobility and quality of life. This study aims to determine the effect ofj jathropha multifida, linn to the number of PMN and selt mast in the process of wound healing in rats with acute injury models. This study is an experimental research laboratory using the design of post test control group design Wistar rats were used as research subjects. Based on Tukey HSD test results, the average number of PMN leukocytes third day the negative control group had no significant difference in the positive control group (0.037) and treatment group (0004). On the seventh day the number of PMN leukocytes negative control group had no significant difference in the positive control group (0.069) and had a significant difference to the treatment group (0.00). Meanwhile, on the fourteenth day the number of PMN leukocytes negative control group had no significant difference in the positive control group (0.000) and had a significant difference to the treatment group (0.00). Based on the results of data analysis Annova one direction on the third day obtained a significant level of 0:50 means there is no significant difference in the number of mast cells in each group on the seventh day. While on day three significant values ​​of 0:08 was also no significant difference, as well as on the fourteenth day found no significant difference between the group with a value of 0.68. Conclusions there was a decrease in the number of Leukocyte PMN in rat wounds given a 10% stem extract ointment, and there was a decrease in the number of mast cells in the wounds of rodents given a 10% stem extract ointment. Suggestions need to be investigated regarding the use of distance stem extract in various concentrations to obtain effective results for wound healing and the need to examine other factors related to wound healing.